SPECULATIVE HYPOTHESES ON POLITICAL DIRECTION OF TOURISM LAW IN INDONESIA; COMMUNITY BASE TOURISM DEVELOPMENT - untari, dhian tyas (Journal of Economic Development, Environment and People, 2022)
Tourism is one sector with a fairly high development potential, even the tourism sector makes a large contribution to GDP and GRDP. According to the Law of the Republic of Indonesia Number 10 of 2009 concerning Tourism and the Regulation of the Minister of Home Affairs Number 33 of 2009 concerning Guidelines for Ecotourism Development in the Regions, it is stated the importance of community participation in tourism development. Based on this, this study aims to; 1). Studying the political direction of tourism law in Indonesia, 2). Mapping the internal and external environment for Community Base Tourism (CBT) development, and 3). Develop speculative hypotheses related to the CBT development strategy. The sources of the study are secondary data originating from books and publications related to Tourism Law Politics and CBT Development. Strategic Management matrix; EFAS/IFAS and Garnd Matrix used in this study. Hope that the results of the study become a influence for next research related to the development of CBT in the perspective of Political Law.